Tactile gating in a reaching and grasping task - Colino, Francisco L. (John Wiley and Sons Inc., 2014)
A multitude of events bombard our sensory systems at every moment of our lives. Thus, it is important for the sensory cortex to gate unimportant events. Tactile suppression is a well‐known phenomenon defined as a reduced ability to detect tactile events on the skin before and during movement. Previous experiments found detection rates decrease just prior to and during finger abduction, and decrease according to the proximity of the moving effector. This study examined how tactile detection changes during a reach to grasp. Fourteen human participants used their right hand to reach and grasp a cylinder. Tactors were attached to the index finger, the fifth digit, and the forearm of both the right and left arm and vibrated at various epochs relative to a “go” tone. Results showed that detection rates at the forearm decreased before movement onset; whereas at the right index finger, right fifth digit and at the left index finger, left fifth digit, and forearm sites did not decrease like in the right forearm. These results indicate that the task affects gating dynamics in a temporally‐ and contextually dependent manner and implies that feed‐forward motor planning processes can modify sensory signals.